2016 38th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2016
DOI: 10.1109/embc.2016.7591700
|View full text |Cite
|
Sign up to set email alerts
|

Augmented reality for breast tumors visualization

Abstract: 3D visualization of breast tumors are shown to be effective by previous studies. In this paper, we introduce a new augmented reality application that can help doctors and surgeons to have a more accurate visualization of breast tumors; this system uses a marker-based image-processing technique to render a 3D model of the tumors on the body. The model can be created using a combination of breast 3D mammography by experts. We have tested the system using an Android smartphone and a head-mounted device. This proo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…[30][31][32] Some studies have also combined preoperative 3D photographs with magnetic resonance imaging data for intraoperative use. 33,34 However, only one other study acquired 3D photographs during surgery (reduction mammoplasty). 35 We demonstrated that 3D photographs can be acquired during reconstruction surgeries within acceptable time limits.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] Some studies have also combined preoperative 3D photographs with magnetic resonance imaging data for intraoperative use. 33,34 However, only one other study acquired 3D photographs during surgery (reduction mammoplasty). 35 We demonstrated that 3D photographs can be acquired during reconstruction surgeries within acceptable time limits.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer in transplantation patients has a similar occurrence to that of the general population but the results of treatment are much inferior [ 44 ]. Quality of Life Technology Labs designed an AR application that uses 3D mammography, breast tumor visualization, which renders its model on the patient’s body, using a head-mounted device and Android smartphone to facilitate screening and planning for breast surgery [ 45 ].…”
Section: Ar In the Assessment Of Anatomical And Pathological Structurmentioning
confidence: 99%
“…Biomechanical modeling of the breast is integral to predicting tumor location across multimodal diagnostic imaging, [1][2][3] surgical planning, 4,5 and surgery. 6,7 Advances in model accuracy have the potential to substantially improve women's health and quality of life. Despite the growing use of breast biomechanical models for different applications, persistent knowledge gaps in both the anatomical and biomechanical literature prevent an accurate model from being developed and deployed for patient-specific applications.…”
Section: Introductionmentioning
confidence: 99%
“…Biomechanical modeling of the breast is integral to predicting tumor location across multimodal diagnostic imaging, 1–3 surgical planning, 4,5 and surgery 6,7 . Advances in model accuracy have the potential to substantially improve women's health and quality of life.…”
Section: Introductionmentioning
confidence: 99%